Multimedia quality transmission evaluation over wireless networks: a survey - Chaari, Hekma; Mnif, Kais; Kamoun, Lotfi (Wireless Networks, 2015)
In recent years, usage of multimedia applications has increased dramatically, especially after the evolution of 3G and 4G technologies. Moreover, the development of new user devices, such as laptops, Smartphone, etc. increased very steeply and rapidly, to support different types of services and different means of communication satisfying user’s needs. Here, the challenge is how to make those services available to users with a high quality; we speak here about quality of service (QoS) and quality of experience. In this survey, we examine different characteristics of wireless networks to determine the enhancements introduced by each technology. Particularly, we focus on the benefits and limitations of three main technologies which are WiMAX, UMTS and LTE, and the role of each one in increasing QoS satisfaction for multimedia application. A comparison is also done between researches already published in Multimedia quality evaluation over wireless networks topic, taking into account some considerations, such QoS parameters, used simulator, assessed applications, etc. All those help us to extract the strengths and limitations of those researches.<br